PENGARUH PENGENDALIAN KONFLIK, BUDAYA ORGANISASI DAN KOMUNIKASI TERHADAP KINERJA PEGAWAI KANTOR PERBEKEL DESA PENARUNGAN - Ni Putu Indah Anggreni; Anak Agung Dwi Widyani; Putu Ayu Sintya Saraswati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
Good employee performance is a step to achieve organizational goals. This study aims to determine the effect of conflict control, organizational culture and organizational culture on employee performance. This research was conducted at the Penarungan Village Repair Office. The sample in this study were 33 people who were employees of the Penarungan Village Repair Office. The method of determining the sample in this study is the saturated sampling method. Data was collected through documentation, interviews and questionnaires. The data analysis technique used in this study is linear regression analysis through the SPSS version 25 program. Based on the results of the analysis, this study shows that conflict control has a positive and significant effect on employee performance at the Penarungan Village Head Office. Organizational culture has a positive and significant effect on employee performance at the Penarungan Village Head Office. Communication has a positive and significant effect on employee performance at the Penarungan Village Perbekel Office.